Rhinogenic Orbital Inflammation - What Has Changed over the Past 50 Years? - Chrobok, Viktor; Pellant, Arnošt; Mandysová, Petra; Mejzlík, Jan; Dědková, Jana; Čelakovský, Petr (Karolinum Press, 2019)
The purpose of the study was to compare the incidence, diagnostics, and treatment of rhinogenic inflammatory complications over the past 50 years. Retrospective study of 292 patients of ENT department, University hospital: Group A treated from 1966 to 1995, Group B treated from 1996 to 2015. RESULTS: Preseptal inflammation was the most common type (73% vs. 74%), followed by subperiosteal abscess (21% vs. 20%). Surgery was indicated in 35% vs. 37% of the patients (p = 0.434). The most commonly used surgical approach was the external route (80%) in Group A and endoscopic endonasal surgery (60%) or a combination of endoscopic surgery of the paranasal sinuses and external orbitotomy (30%) in Group B (p < 0.001). The percentage of reoperations was 13% vs. 14%. In cases of revision surgery, the orbit was always treated using the external surgical approach. Complete recovery was achieved in 92% and 98.5% of the patients belonging to Group A and B, respectively (p = 0.622). CONCLUSION: Nowadays, the endoscopic endonasal approach is the most frequently used surgical technique for paranasal sinuses. The technique used to treat the orbital complication itself depends on several factors. Nowadays, the endoscopic approach is preferred. The external approach can be considered in the case of recurrent or persistent abscesses, especially if they are located in the upper or the lateral part of the orbit.
Rinogenní očnicové komplikace – co se změnilo za posledních 50 roků?
Keywords: sinusitis; sinusitis; endoscopic surgery; orbital inflammation; endoskopická chirurgie; očnicové komplikace